A Simple Activity Exploring the Social Construction of Race - Kwenda, Maxwell (TRAILS: Teaching Resources and Innovations Library for Sociology, 2012)
This exercise demonstrates the social construction of the concept of race as it is used in different societies. It reduces the concept of race to a social fact using the analogy of shaded circles. This depersonalizes the topic and allows for an in-depth examination of the processes involved in creating the concept of race that many would consider normal and even natural. I have found over the years that more students are able to figure out how it is that race has biological attributes but is socially defined with differential consequences.